Changes in annual, seasonal and monthly rainfall in Nigeria during 1961-90 and consequences to agriculture - Jagtap, S.S. (1995)
The focus of this study is to provide baseline data for agricultural development activities in Nigeria, with emphasis on understanding the dynamics of spatial and temporal change in annual, seasonal and monthly rainfall during the past 30 years (1961-1990), using daily rainfall data. It was found that annual rainfall has declined in Nigeria over both time and space. The rainfall decline is unprecedented in duration and seasonal expression. The greatest change occurred in the onset of the rainy season and the extent of early rainfall, which has resulted in a reduction of the growing season by nearly one month and is likely to increase risk in early planting. There were fewer wet days and higher rainfall intensities in most of the country. This may cause erosion and emphasizes the need for improved measures to arrest erosion. There are also several agricultural technologies available that could help farmers reduce the negative impacts of rainfall on crop production.